PEMANFAATAN MARKETPLACE MEDIA SOSIAL SEBAGAI SARANA PROMOSI PRODUK UMKM PADA KELOMPOK INFORMASI MASYARAKAT KABUPATEN BANTUL - Ariyana, Renna Yanwastika; Haryani, Prita; Fatkhiyah, Erfanti (DHARMA BAKTI, 2021)
The growing development of Information and Communication Technology (ICT), especiallywith the presence of the internet has an impact on various aspects of life including trade.The rapid development of online stores has made some social media develop marketplacefeatures as a means of buying and selling transactions. Marketplace with a wider marketreach and no time limit makes it a good choice in marketing products. Providing knowledgeon how to market products via the internet can provide the community with ways to promoteproducts through marketplace features available on social media. The implementation ofcommunity service carried out at the Communication and Information Office (KOMINFO)of Bantul Regency aims to provide knowledge to the community on how to promote Microand Small Medium Enterprises (MSME) products through social media. From the results ofdiscussions with administrators and the Village Apparatus Operators (VAO) representingthe Community Information Group (CIG) in Bantul district, the community does not yet knowmuch about how to promote MSME products in each village through social media.Therefore, through this community service activity VAO representing CIG in Bantul districtis equipped with ways to promote products through social media.